مقدرة خام الزيوليت الطبيعي السوري على ربط وتحرير الأمونيوم وتأثيره على استجابة نبات عشب النجيل (Rye-grass) للآزوت (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
The objective of this study was to evaluate the ability of Natural Syrian Zeolite Ore (NSZO) to bind and release ammonium ions, and to evaluate its effect on Rye-grass response to NH4-N nitrogen. The research was carried out by studying ammonium adsorption by the use of batch experiments and the application of Langmuir and Freundlich models. Both models predict ammonium adsorption with high correlation (R2>0.95). A desorption study was followed over time using 2M KCl aquice solution, Results showed that total adsorbed ammonium was released within 5 hours. Ammonium adsorption kinetics was studied using pseudo first order and Intra particle diffusion models in order to predict ammonium adsorption kinetics. Results demonstrate that both models could predict ammonium adsorption during first period of adsorption processes.. Intra particle diffusion model was efficient in predicting adsorption kinetics when adsorption process progressed up to 300 min. In order to study Rye-grass response to nitrogen loaded on NSZO as ammonium, a pot experiment was carried out using two sources of nitrogen. Ammonium loaded on zeolite, or as ammonium chloride fertilizer. Pots receive the same amount of nitrogen in either forms. on zeolite. Results showed an increase growth response of rye-grass when ammonium supply was  loaded on zeolite as N source. يهدف البحث لاختبار قدرة خام الزيوليت الطبيعي السوري على ربط وتحرير الأمونيوم وتقييم استجابة نبات عشب النجيل Rye-Grass للآزوت. نفذ البحث من خلال دراسة ادمصاص الأمونيوم على خام الزيوليت باستخدام طريقة الادمصاص على دفعات الـ batch experiment، وبتطبيق موديلي فريندلش ولانغمير، حيث استطاع كلا الموديلين التنبؤ بالعملية الادمصاصية للأمونيوم حيث كانت جودة العلاقةR2>0.95) ). كذلك نفذت تجربة تحرير الأمونيوم المدمص على خام الزيوليت باستخدام محلول كلوريد البوتاسيوم KCl بتركيز 2 مول/ليتر خلال أزمنة تلامس متزايدة، حيث  تحرر كامل الأمونيوم المدمص بعد حوالي 5 ساعات. دُرست حركية ادمصاص الأمونيوم على خام الزيوليت وطبق الموديل الخطي الكاذب من الدرجة الأولىpseudo first  orderوموديل الانتشارية البينية  Intra particle diffusionللتنيؤ بحركية الادمصاص، لقد استطاع كلا الموديلين التنبؤ بالحركية خلال الأزمنة الأولى لعملية الادمصاص، لكن كان موديل الانتشارية البينية أكثر كفاءة في التنبؤ بحركية الادمصاص مع تقدم زمن الادمصاص إلى 300 دقيقة. بهدف دراسة استجابة عشب النجيل للآزوت المحمل على خام الزيوليت على شكل أمونيوم نفذت تجربة أصص باستخدام مصدرين للآزوت، إما محمل على الزيوليت على شكل أمونيوم مدمص أو على شكل سماد NH4Cl حيث تلقت المعاملات ذات الكمية من الآزوت المحمل على الزيوليت. بينت النتائج ارتفاع الاستجابة المتمثلة بالإنتاج الجاف عندما كان مصدر الآزوت هو الأمونيوم المحمل على الزيوليت.